Knowledge, Practices, and Factors Influencing Exclusive Breastfeeding Among Slum Mothers in Kathmandu Valley - Khadka, Sumitra (Pragnya Sarathi, 2026)
Feeding a baby only breast milk for 6 month of life refers exclusive breast feeding. It is essential for infants' growth, immunity and mental health. However, literature shows that slum settlements follow traditional way and remain unchanged. This paper explores knowledge, practices, and factors influencing exclusive breast feeding in the context of Settlements of Kathmandu. The cross-sectional research design was used in research. A quantitative dominant mixed-methods was employed. Survey questionnaire, integrated open-ended questions was used. One hundred forty-one mothers were participated in survey. Descriptive statistics and chi-square test were utilized to analyze the data. Finding shows that 94.3% mother were currently breastfeeding. 61% practiced exclusive breastfeeding 4-6 months. 62.4% used other supplement liquid. Although 57.4% had heard of exclusive breastfeeding. Among the 57.4 % have heard exclusive breast feeding and 29.1% correctly know six months as recommended. Chi-square test result shows that, no statistically significant association between awareness and breastfeeding practices (p>0.05). Work load, perceived insufficient breast milk, family influence, hygiene- related difficulties, and limited support systems affected exclusive breast feeding. Study concluded that awareness along is insufficient to ensure recommended exclusive breastfeeding practice in slum settlements. Change belief, enhance awareness and improving economic status contribute to improve the exclusive breast feeding.